2021
DOI: 10.3390/ani11082452
|View full text |Cite
|
Sign up to set email alerts
|

Temperament Predicts the Quality of Social Interactions in Captive Female Rhesus Macaques (Macaca mulatta)

Abstract: Previous reports suggest that female macaques with greater similarity in emotionality and nervous temperament, as evaluated in a well-established BioBehavioral Assessment (BBA) at the California National Primate Research Center, were more likely to form successful pairs. We tested whether the same measures can also predict the quality of social interactions among 20 female rhesus macaque pairs. We correlated the pairs’ emotionality and nervous temperament scores obtained in infancy and the levels of behaviors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 77 publications
2
4
0
Order By: Relevance
“…Our findings provide strong support to the value of the ELBT scoring system, which has also been used to predict the quality of social interactions in rhesus macaques and improve quality of life through the formation of successful social pairings (Pomerantz & Capitanio, 2021). The ELBT scores can be used to identify animals that are at high risk for developing CE during infancy, and steps can be taken to ensure their welfare and longevity.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our findings provide strong support to the value of the ELBT scoring system, which has also been used to predict the quality of social interactions in rhesus macaques and improve quality of life through the formation of successful social pairings (Pomerantz & Capitanio, 2021). The ELBT scores can be used to identify animals that are at high risk for developing CE during infancy, and steps can be taken to ensure their welfare and longevity.…”
Section: Discussionsupporting
confidence: 68%
“…Our findings provide strong support to the value of the ELBT scoring system, which has also been used to predict the quality of social interactions in rhesus macaques and improve quality of life through the formation of successful social pairings (Pomerantz & Capitanio, 2021).…”
Section: Ce and Elbtsupporting
confidence: 67%
“…Pair housing is a common form of captive animal housing that involves pairing two animals together with either full or protected access to each other and has proven a relatively effective strategy for maximizing animal welfare while still complying with regulatory guidelines that mandate nonhuman primates be socially housed whenever possible (Baker et al, 2012; DiVincenti & Wyatt, 2011; Truelove et al, 2017). Although there are many factors that should be considered when deciding which animals to house together (e.g., the age, sex, dominance rank, reproductive status), several studies in macaques have shown that pairing animals together (typically same‐sex peers) based on similarities in personality/temperament can be an effective strategy for facilitating stable pairings (Capitanio et al, 2017; Coleman, 2012; Pomerantz & Capitanio, 2021). These results suggest that compatibility is not only important for pair‐bonding relationships but may also be an important factor in shaping other kinds of social relationships in nonhuman primates.…”
Section: Discussionmentioning
confidence: 99%
“…Within studies on positive biology, the instructive role of mild negative episodes is recognised as contributing to positive outcomes, as seen, for example, in low-stress stock-handling methods (Grandin 2004), a point Ryff (2022) noted that is often overlooked in human positive psychology, but is now being acknowledged in its so-called second wave (Lomas 2016). The importance of positives is captured by the observations that positive health is more than the absence of ill-health (Ayres 2020) and that social wellbeing is more than freedom from social isolation (Pomerantz and Capitanio 2021), as recognised by WHO (1946). Thus, positive biology is more than a semantic distinction between 'good' and 'positive' to be the study of processes lying outside the domain of 'host defence mechanisms' that equip the animal with a capacity to flourish.…”
Section: What Is Wellbeing?mentioning
confidence: 99%